Analisis Strategi Penentuan Harga Dalam Pemasaran Internasional - Winda Suciani Siregar; Nuri Aslami (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2021)
Moderate international marketing is better known as international trade, where activities that occur involve physical and non-physical merchandise such as services. In marketing management, one of the important things is pricing. Price can be classified as a tactical variable. This is because the price is a value that can change. If a company creates a product that has benefits for the community, then the company must determine the price related to the product that has been created. In this research, literature study method is used from journals, articles, books, and other relevant sources. The conclusion that can be drawn is that pricing strategies are important in relation to international marketing. If the pricing strategy is not properly implemented, you will get a minimum profit or worse, you will get a loss like PT. Mustika Ratu in Saudi Arabia. Meanwhile, if the pricing strategy has been implemented properly and appropriately, it will certainly benefit. Pricing strategies can be done with discounts or rebates as well as promotions.